Breaking Down the Coercive Cycle: How Parent and Child Risk Factors Influence Real-Time Variability in Parental Responses to Child Misbehavior. (1st October 2016) - Lunkenheimer, Erika; Lichtwarck-Aschoff, Anna; Hollenstein, Tom; Kemp, Christine J.; Granic, Isabela
SYNOPSIS: Objective . Parent–child coercive cycles have been associated with both rigidity and inconsistency in parenting behavior. To explain these mixed findings, we examined real-time variability in maternal responses to children's off-task behavior to determine whether this common trigger of the coercive cycle (responding to child misbehavior) is associated with rigidity or inconsistency in parenting. We also examined the effects of risk factors for coercion (maternal hostility, maternal depressive symptoms, child externalizing problems, and dyadic negativity) on patterns of parenting. Design. Mother–child dyads ( N  = 96; M child age = 41 months) completed a difficult puzzle task, and observations were coded continuously for parent (e.g., directive, teaching) and child behavior (e.g., on-task, off-task). Results . Multilevel continuous-time survival analyses revealed that parenting behavior is less variable when children are off-task. However, when risk factors are higher, a different profile emerges. Combined maternal and child risk is associated with markedly lower variability in parenting behavior overall (i.e., rigidity) paired with shifts toward higher variability specifically when children are off-task (i.e., inconsistency). Dyadic negativity (i.e., episodes when children are off-task and parents engage in negative behavior) are also associated with higher parenting variability. Conclusions . Risk factors confer rigidity in parenting overall, but in moments when higher-risk parents must respond to child misbehavior, their parenting becomes more variable, suggesting inconsistency and ineffectiveness. This context-dependent shift in parenting behavior may help explain prior mixed findings and offer new directions for family interventions designed to reduce coercive processes.